Nutrient requirement and nutritive value of Cynodon dactylon (L.) Pers. Cv. Coast-cross no 1 - Silva, Ana Luisa Palhano; Haddad, Cláudio Maluf (Pesquisa Agropecuaria Brasileira, 1992)
The objectives of this work were to study the coast-cross no 1 bermudagrass (Cynodon dactylon (L.) Pers.) mineral composition in relation to cutting date and to find the relationship between its nutritive value and stage of maturity. The treatments consisted of six growth periods (20, 30, 40, 50, 60 and 70 days). A random design was used, with four replications. Dry matter increased quadratically (P < 0,05) between days 20 and 70 of growth. In vitro dry matter digestibility decreased and NDF and ADF values increased (P < 0,05), both with a quadratic trend. A linear decrease (P < 0,05) in all macronutrients but P levels with time was observed. Phosphorus concentration decreased quadratically (P < 0,05). The concentration of B, Mn and Fe were not significantly (P < 0,05) affected by cutting date. As a conclusion, it can be stated that the result of an association between dry matter yield and digestibility values for Coast-cross no 1 bermudagrass, between days 30 and 40 of growth, is adequate when compared to an accepted forage quality pattern.